Effect of post harvest application of chemicals and different packaging materials on shelf-life of banana (Musa spp) cv Robusta - SAHAY, SANJAY; MISHRA, P K; RASHMI, K; AHMAD, M FEZA; CHOUDHARY, A K (The Indian Journal of Agricultural Sciences, 2015)
An experiment was conducted in Department of Horticulture (Fruit and Fruit Technology), Bihar Agricultural College, Sabour, Bihar during 2010-11 to delay ripening and extend shelf-life of banana (Musa paradisiaca L.) fruit. The experiments were undertaken with twelve treatments combinations of CaCl2 (2% or 4%), polyethylene bag, banana dried leaves, newspaper, CaCl2 (2%) + polyethylene bag, CaCl2 (4%) + polyethylene bag, CaCl2 (2%) + banana dried leaves, CaCl2 (4%) + banana dried leaves, CaCl2 (2%) + newspaper, CaCl2 (4%) + newspaper and control. CaCl2 (4%) and CaCl2 (2%) in combination with polyethylene bag were the most potent treatment for enhancing storage period and maintaining physico-chemical characteristics of banana cv Robusta while as CaCl2 (4%) + polyethylene bag were very effectively reduced physiological loss in weight (PLW) and ripening per cent. The maximum retention of bio-chemical constitute like total soluble solids, titratable acidity, and reducing sugars was also obtained in fruits treated with CaCl2 (4%) + polyethylene bag along with increased shelf-life up to 16th day storage period of banana fruits.